Low pertussis antibody levels in maternal and umbilical cord blood samples in Turkey - Türkoğlu, Ebru; Sönmez, Cemile; Özer, Esra; Çöplü, Nilay; Kurugöl, Zafer (The Turkish Journal of Pediatrics, 2016)
Pertussis continues to cause significant mortality and morbidity in many countries despite high vaccine coverage, especially among young infants. The aim of the study was to determine pertussis antibody levels in paired maternal and cord blood samples, to evaluate the placental transfer of these antibodies, and to assess whether newborn infants have adequate antibody levels against pertussis. Antibody titers to pertussis toxin (anti-PT) and filamentous hemagglutinin (anti-FHA) were measured by in-house enzyme linked immunosorbent assay (ELISA) in 251 paired maternal delivery and cord blood samples. Geometric mean concentrations (GMCs) of pertussis antibodies and cord:maternal GMC ratios were calculated. GMCs of maternal anti-PT and anti-FHA antibodies at delivery were 4.12 and 9.89 EU/ml, respectively. Cord GMCs were 133% and 131% of maternal delivery values for PT and FHA, respectively; demonstrating effective placental transfer. However, cord pertussis antibodies were at a low concentration; 5.49 EU/ml for PT and 12.73 EU/ml for FHA. Only 34.6% of infants had protective anti-PT levels (≥10 EU/ml) at birth. Anti-pertussis antibody concentrations were extremely low in pregnant women in Turkey where childhood pertussis vaccination coverage has been high for a long time. Despite effective placental antibody transfer, umbilical cord pertussis antibody concentrations are similarly low. A majority of young infants are vulnerable to pertussis infection until the onset of primary vaccinations. These data support the need for pertussis vaccination during pregnancy to prevent infant infection in Turkey.